Prevalence and antimicrobial susceptibility of Enterococcus spp. in ready-to-eat salads (dips), the environment and the personnel of a salad processing plant in Northern Greece - SERGELIDIS, D; ABRAHIM, A; ANAGNOSTOU, V; PAPA, A; PAPADOPOULOS, Th. (Journal of the Hellenic Veterinary Medical Society, 2018)
A total of 225 samples from the dips (cheese, roe, egg plant and tzatziki dip), the environment and the handlers of a salad manufacturing plant in Northern Greece were examined for the presence and antibiotic susceptibility of Entervcocccus spp. Enterococcus faecium was the isolated species from 12% of the samples. 38.1% and 15% of egg plant and cheese dip samples were positive, respectively. Among the dip ingredients, 30% of mayonnaise, 20% of feta cheese and 10% of myzithra were positive. Positive were, also, 8.6 % of the environmental samples, 20% from handlers’ skirts, 20% from handlers’ gloves and 16.7% from their nasal cavity. All isolates were sensitive to glycopeptides (vancomycin and teicoplanin). Isolates from handlers’ nasal cavities were resistant to penicillin and ampicillin, while one of them was, also, resistant to chloramphenicol. All isolates from the environment, the dips and their ingredients were susceptible to these three antibiotics, but they presented resistance to more than 3 antibiotic categories. Ready-to-eat foods may be potential source of contamination to humans of multidrug resistant enterococci. Further research is needed to elucidate their epidemiology in these foods.